2023
DOI: 10.7554/elife.85800
|View full text |Cite
|
Sign up to set email alerts
|

Dermal appendage-dependent patterning of zebrafish atoh1a+ Merkel cells

Abstract: Touch system function requires precise interactions between specialized skin cells and somatosensory axons, as exemplified by the vertebrate mechanosensory Merkel cell-neurite complex. Development and patterning of Merkel cells and associated neurites during skin organogenesis remains poorly understood, partly due to the in utero development of mammalian embryos. Here, we discover Merkel cells in the zebrafish epidermis and identify Atonal homolog 1a (Atoh1a) as a marker of zebrafish Merkel cells. We show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 116 publications
(193 reference statements)
1
18
0
Order By: Relevance
“…Staging of zebrafish post-embryonic development relies on standard length (SL) in millimeters, with sexual maturity attained ∼18 mm SL (Parichy et al, 2009). Cells with the prototypical MC morphology—spherical with actin-rich, microvillar protrusions of ∼1-2 microns in length— populate several adult zebrafish skin compartments, including trunk skin ( Figure 1A,B ; (Brown et al, 2023)). Atonal homolog 1 ( Atoh1 ) encodes a transcription factor necessary and sufficient for murine MC development (Morrison et al, 2009; Ostrowski et al, 2015; Van Keymeulen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Staging of zebrafish post-embryonic development relies on standard length (SL) in millimeters, with sexual maturity attained ∼18 mm SL (Parichy et al, 2009). Cells with the prototypical MC morphology—spherical with actin-rich, microvillar protrusions of ∼1-2 microns in length— populate several adult zebrafish skin compartments, including trunk skin ( Figure 1A,B ; (Brown et al, 2023)). Atonal homolog 1 ( Atoh1 ) encodes a transcription factor necessary and sufficient for murine MC development (Morrison et al, 2009; Ostrowski et al, 2015; Van Keymeulen et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Atonal homolog 1 ( Atoh1 ) encodes a transcription factor necessary and sufficient for murine MC development (Morrison et al, 2009; Ostrowski et al, 2015; Van Keymeulen et al, 2009). Zebrafish atoh1a is an ortholog of murine Atoh1 , and zebrafish MCs express reporters inserted into the upstream region of the atoh1a locus (Brown et al, 2023). Using a nuclear localized atoh1a reporter to label MCs, we previously found that trunk MCs begin to appear during the onset of squamation (scale formation) at approximately 9 mm SL and rapidly increase in density from 10-15 mm SL (Brown et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations